Tinjauan Studi: Efektivitas Model Expected Credit Loss (ECL) IFRS 9 dalam Mengatasi Procyclicality dan Mendukung Stabilitas Keuangan - Muhammad Rizal; Yessica Amelia; Sarah Fitriyani (Jurnal Bisnis Inovatif dan Digital, 2024)
This study examines procyclicality and the Expected Credit Loss (ECL) model in IFRS 9, aiming to analyze the effectiveness of accounting policies in reducing financial instability. Using a qualitative literature review approach, this research reviews various studies related to the implementation of IFRS 9, particularly in the context of the recognition of expected credit losses. The ECL model is expected to reduce the impact of excessive economic cycles by accounting for credit losses from the outset, in contrast to the previous IAS 39 model. While there are challenges in the accuracy of loss estimates and varying implementation across countries, the findings suggest that IFRS 9 has the potential to enhance global financial system stability, provided it is applied carefully. The study also identifies several limitations that need to be considered for further research development.